2009
DOI: 10.1021/la904139b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water on Aggregation and Stability of Monoglycerides in Hydrophobic Solutions

Abstract: We apply a set of different techniques to analyze the physical properties and phase transitions of monoglyceride (MG)-oil-water ternary systems. The effect of MGs on water absorption in food-grade hazelnut oil and in pure hydrocarbon oil (decane) is reported. Comparison between decane and hazelnut oil backgrounds indicates that the effect of water absorption is significant and universal in different MG ternary systems. Adding small amounts of cosurfactant (stearic acid) is necessary to stabilize the MGs in oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…M a n u s c r i p t 6 The data are summarised in Table 3, from which it is clear that the d spacing for L β1 phase increases continuously with water content up to 50 w/w% then the spacings do not increase further with more water addition. Thus, the maximum swelling capacity of the mixture of monoglycerides in water is obtained at 50 w/w% water content [28].…”
Section: Resultsmentioning
confidence: 94%
“…M a n u s c r i p t 6 The data are summarised in Table 3, from which it is clear that the d spacing for L β1 phase increases continuously with water content up to 50 w/w% then the spacings do not increase further with more water addition. Thus, the maximum swelling capacity of the mixture of monoglycerides in water is obtained at 50 w/w% water content [28].…”
Section: Resultsmentioning
confidence: 94%
“…When water activity is increased, metals are mobilized and oil viscosity is reduced hence oxidation is accelerated . Different water types or concentrations and levels of emulsifiers produce different shapes of association colloids and affect lipid oxidation differently . It was found that phospholipids synergize the activity of α‐tocopherol only in the presence of small amounts of water and catalysis by water‐soluble radical generators .…”
Section: The Supramolecular Chemistry Of Lipid Oxidationmentioning
confidence: 99%
“…In the oil system, below the gelation transition temperature, the inverse lamellar phase is formed with a definite hexagonal in-plane ordering and, below that point, a sub-α crystalline structure is seen [17,18]. In MAG-oilwater systems there are hydrogen bond interactions that stabilize the structure and a lamellar gel is formed [19].…”
Section: Introductionmentioning
confidence: 99%